The potential implication of MDR1 and NAC1 genetic polymorphisms on resistance to antiepileptic drugs among a Jordanian epileptic population: a cross-sectional study - Rami Abduljabbar; Duaa Eid Tamimi; Al-Motassem Yousef (Taylor & Francis Group, 2023)
Background Resistance to antiepileptic drugs (AEDs) remains one of the main challenges to neurologists. Polymorphisms of drug efflux transporters such as multidrug resistance (MDR1) gene and target sites such as the nucleus accumbens-associated 1 (NAC1) gene have been suggested to influence the responsiveness to treatment. Aim Evaluation of the association of MDR1 and NAC1 polymorphisms with AEDs resistance among Jordanian epileptic patients. Subjects and methods 86 Jordanian epileptics were included in the study. DNA was extracted and genotyping was conducted by polymerase chain reaction followed by sequencing. Nine single nucleotide polymorphisms (SNPs) on the MDR1 gene and six SNPs on the NAC1 gene were investigated. Results MDR1 and NAC1 polymorphisms don't seem to influence the resistance to AEDs at the genotype or allele level. However, a strong association was found between MDR1 rs2032588 (OR = 5; 95%CI = [1.3-18.8], p = 0.01) and AEDs resistance among males at the allele level. Also, data revealed an association between MDR1 rs1128503 and AEDs resistance among females at the allele level. Conclusion The data suggest that MDR1 and NAC1 polymorphisms do not influence the AEDs resistance among Jordanian epileptics. However, there is a gender-dependent association between MDR1 polymorphisms and resistance to AEDs at two SNPs (rs2032588 and rs1128503).